2001
DOI: 10.1074/jbc.m007394200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the N-Ethylmaleimide-sensitive Factor Is Associated with Depolarization-dependent Neurotransmitter Release from Synaptosomes

Abstract: Critical to SNARE protein function in neurotransmission are the accessory proteins, soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein (SNAP), and NSF, that play a role in activation of the SNAREs for membrane fusion. In this report, we demonstrate the depolarization-induced, calcium-dependent phosphorylation of NSF in rat synaptosomes. Phosphorylation of NSF is coincident with neurotransmitter release and requires an influx of external calcium. Phosphoamino acid analysis of the radiolabeled NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 69 publications
(78 reference statements)
1
45
1
Order By: Relevance
“…It is consistent with the report that TrkB receptor directly activates this protein kinase (51). In particular, the activation of PKC is noteworthy because Matveeva et al (52) demonstrated that PKC, which is activated by a calcium influx, phosphorylates NSF. A similar process might be recruited in the BDNF-dependent interaction between NSF and the AMPA receptor subunit.…”
Section: Discussionsupporting
confidence: 79%
“…It is consistent with the report that TrkB receptor directly activates this protein kinase (51). In particular, the activation of PKC is noteworthy because Matveeva et al (52) demonstrated that PKC, which is activated by a calcium influx, phosphorylates NSF. A similar process might be recruited in the BDNF-dependent interaction between NSF and the AMPA receptor subunit.…”
Section: Discussionsupporting
confidence: 79%
“…We now add an additional layer of regulation to the process of exocytosis, that of modulating the disassembly or priming of cis-SNARE complexes on secretory granules. It is interesting to speculate that even NSF activity is regulated during mast cell signaling; however, there are only limited data to suggest that this occurs (47). It is also important to point out that even if NSF activity were regulated during exocytosis, our data do not allow us to discern whether the importance of SNARE priming is an early event in exocytosis or is one of the events proximal to granule-plasma membrane fusion.…”
Section: Discussioncontrasting
confidence: 42%
“…In addition to answering a long-standing question about the timing of NSF action during SV trafficking, our results indicate a potential locus for rapid regulation of neurotransmitter release by nitric oxide (30) or protein phosphorylation (64)(65)(66). Our work also defines the precise timing of a proteinprotein interaction important for SV exocytosis, which will provide a temporal benchmark for future studies of the timing of other exocytotic interactions.…”
Section: Discussionmentioning
confidence: 89%